A framework of heterogeneous cloud service and multi attributes negotiation using double auction - Muhamad Hariz Muhamad Adnan (Tanjong Malim, 2020)
A framework of heterogeneous cloud service and multi attributes negotiation using double auction by Muhamad Hariz Muhamad Adnan